Indonesia’s Badminton National Referees: What is The Level of Self-Confidence and Concentration? - PRATIWI, ERA; SUHARJANA; DHARMA HITA, I PUTU AGUS; SARI, HELEN PURNAMA; ARIESTIKA, ELSA (Innovare Journal of Education, 2022)
Important national referees have psychological aspects, especially confidence and concentration when leading the match. This study aims to understand the confidence and concentration of badminton national referees in leading matches. This type of research is descriptive quantitative. The population of this research is all 140 Indonesian national badminton referees with national licenses A and B. The sample technique used in this research is using purposive sampling technique with the number of subjects used in this study are 26 national referees A and B. The instrument used is a self-confidence questionnaire. and referee concentration as many as 32 statements. The data analysis technique in this study used a validity test measured by the correlations product moment technique and a reliability test using the Cronbach's alpha technique. From the validity test, the value of sig 0.004 was obtained for the confidence questionnaire and sig 0.000 for the concentration questionnaire. The results of the reliability test obtained a value of 0.871 for the self-confidence questionnaire and a value of 0.975 for the concentration questionnaire. The results showed that the level of self-confidence was 1 person (4%) in very low category, 2 (8%) in moderate category, 4 (15%) in high category, and 19 (73%) in very high category. As for the concentration level, there are 7 (27%) very low categories, 4 (15%) low categories, 4 (15%) high categories, and 11 (42%) very high categories.